2019
DOI: 10.3390/inventions4030043
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Covariance Matrix Sampling on the Angle of Arrival Estimation Accuracy

Abstract: Several works show that the linear Angle of Arrival (AoA) methods such as Projection Matrix (PM) have low computational complexity compared to the subspace methods. Although the PM method is classified as a subspace method, it does not need decomposition of the measured matrix. This work investigates the effect of the sampled columns within the covariance matrix on the projection matrix construction. To the authors' knowledge, this investigation has not been addressed in the literature. Unlike the subspace met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…In a previous works [32,37], the impact on the estimation accuracy and the Probability of Detection (PoD) of AoAs of the number of sampled columns (size of the sampled matrix) that was used in the projection matrix construction has been analysed and investigated. It was demonstrated that an increase in the number of the sampled columns leads to increases in the estimation resolutions and PoD.…”
Section: The Reduced Uniform Projection Matrix (Rupm) Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous works [32,37], the impact on the estimation accuracy and the Probability of Detection (PoD) of AoAs of the number of sampled columns (size of the sampled matrix) that was used in the projection matrix construction has been analysed and investigated. It was demonstrated that an increase in the number of the sampled columns leads to increases in the estimation resolutions and PoD.…”
Section: The Reduced Uniform Projection Matrix (Rupm) Methodsmentioning
confidence: 99%
“…The distribution and locations of these columns under this method can be represented conceptually as shown in Figure 2; the blue lines represent the locations of the selected columns in the CM. The projection matrix can be computed as follows [37]:…”
Section: Matrixmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, for complexity reduction purposes, it is possible to utilize L columns from the obtained CM to form such a projection matrix instead of using the complete CM or decomposing it [5]. It has been demonstrated that any increase in the number of sampled columns has a positive impact on the effectiveness of the projection matrix construction through improving the estimation accuracy and Probability of Successful Detection (PSD) [33], [34]. However, the complexity of construction will rise.…”
mentioning
confidence: 99%